Comparison of non-maximal tests for estimating exercise capacity - Alajmi, Reem A. (Array, 2020)
Although maximal incremental exercise tests (GXT) are the gold standard for outcome assessment and exercise prescription, they are not widely available in either fitness or clinical exercise programs. This study compared the prediction of VO2max in healthy, sedentary volunteers using a non-exercise prediction (Matthews et al., 1999), RPE extrapolation to 19 and 20 and the Rockport Walking Test (RWT), and of ventilatory threshold (VT) using the Talk Test and RPE @ 13,14,15. Subjects performed a treadmill GXT with gas exchange, a submaximal treadmill with RPE and Talk Test, the RWT and Matthews. All methods provided reasonable estimates of both VO2max and VT, with correlations of >0.80 and SEE~1.3 METs. VO2max was best estimated with the extrapolation to RPE=19. VT was intermediate between the TT Last Positive and Equivocal stages and between RPE 13 and 14. Non-maximal evaluation can be used in place of maximal GXT with gas exchange to make reasonable estimates of both VO2max and VT.